Influence of tennis racquet kinematics on ball topspin angular velocity and accuracy during the forehand groundstroke - Kwon, S.; Pfister, R.; Hager, R. L.; Hunter, I.; Seeley, M. K. (Journal of Sports Science & Medicine, 2017)
Forehand groundstroke effectiveness is important for tennis success. Ball topspin angular velocity (TAV) and accuracy are important for forehand groundstroke effectiveness, and have been extensively studied, previously; despite previous, quality studies, it was unclear whether certain racquet kinematics relate to ball TAV and shot accuracy during the forehand groundstroke. This study evaluated potential relationships between (1) ball TAV and (2) forehand accuracy, and five measures of racquet kinematics: racquet head impact angle (i.e., closed or open face), horizontal and vertical racquet head velocity before impact, racquet head trajectory (resultant velocity direction, relative to horizontal) before impact, and hitting zone length (quasi-linear displacement, immediately before and after impact). Thirteen collegiate-level tennis players hit forehand groundstrokes in a biomechanics laboratory, where racquet kinematics and ball TAV were measured, and on a tennis court, to assess accuracy. Correlational statistics were used to evaluate potential relationships between racquet kinematics, and ball TAV (mixed model) and forehand accuracy (between-subjects model; a = 0.05). We observed an average (1) racquet head impact angle, (2) racquet head trajectory before impact, relative to horizontal, (3) racquet head horizontal velocity before impact, (4) racquet head vertical velocity before impact, and (5) hitting zone length of 80.4 ± 3.6°, 18.6 ± 4.3°, 15.4 ± 1.4 m·s-1, 6.6 ± 2.2 m·s-1, and 79.8 ± 8.6 mm, respectively; and an average ball TAV of 969 ± 375 revolutions per minute. Only racquet head impact angle and racquet head vertical velocity, before impact, significantly correlated with ball TAV (p < 0.01). None of the observed racquet kinematics significantly correlated to the measures of forehand accuracy. These results confirmed mechanical logic and indicate that increased ball TAV is associated with a more closed racquet head impact angle (ranging from 70 to 85°, relative to the ground) and increased racquet head vertical velocity before impact.